Relation between Glycemic Control among the Patients with Type 2 DM and Level of Blood Pressure - Amin, Md Al; Zannat, Tahira; Uddin, Md Nazim; Md Moniruzzaman, -; Md Habibullah, -; Kabir, AKM Humayon; Karim, Md Enamul (Journal of Medicine, 2021)
Introduction: Inadequate glycemic control among patients with type 2 diabetes constitutes a major public health problem and risk factor for the development of diabetes related complications. Hypertension is a common co-morbid condition of diabetes. Hypertension as a factor for poor glycemic control in diabetes patients has not been properly evaluated in Bangladesh. The aim of the study was to assess status of glycemic control among patients with Type 2 DM depending on the level of blood pressure in a tertiary care hospital. Method: This cross sectional study was carried out among 200 adult patients of either gender with type 2 diabetes mellitus, in the Department of Medicine and endocrinology, Dhaka Medical College Hospital from January to June 2015. Results: The mean age of the respondents were 56.85(±10.84) years, ranging from 35 to 77 years. Among 200 patients, 129 (64.5%) were hypertensive and 71 (35.5%) were normotensive with a mean duration of hypertension was 10.03 (±3.39) years. The mean HbA1c for all diabetic, hypertensive and normotensive patients were 7.41% (±1.35), 7.63% (±1.30) and 7.02% (±1.37) respectively. The mean HbA1c was significantly higher in hypertensive than normotensive group (p=0.002). The mean HbA1c was also significantly higher in patients with duration of hypertension (p=0.03) for more than 10 years and in patients who used beta blocker (p=0.005) and diuretics (p=0.02) as hypertensive medication. Among the patients with normal BMI and on dietary modification, those who were hypertensive had significantly higher (p=0.00008) mean HbA1c (7.12(±0.99)) than those were normotensive (5.01(±0.01)). Conclusion: The glycemic control in type 2 DM is found to be poor among the hypertensive patients. There is a complex association of multiple factors like age, gender, duration of hypertension and medications strongly influence the glycemic control of type 2 diabetics with hypertension. J MEDICINE JAN 2021; 22 (1) : 12-17